Ali Jum‘ah’s Legal Meaning Construction for Reading Gharar-Based Labeling in Hidden Fees - Moh Tamtowi; Muhamad Ulul Albab Musaffa (Az-Zarqa': Jurnal Hukum Bisnis Islam, 2026)
Contemporary Islamic business law (muāmalāt) discourse often faces digital transactions by applying familiar legal categories such as gharar, tadlīs, bāṭil, or tarāḍī. Such categories remain important, but they require a careful bridge between legal qur’anic wording, classical interpretive traditions, and modern transaction structures. Using a normative doctrinal method and a legal-semantic juridical approach, this article reconstructs the meaning of akl al-amwāl bi al-bāṭil through four analytical layers: lexical meaning, social usage, legal meaning in Qur’anic usage, and legal operational terminological indicators. These four layers of meaning is synthetized from Sheikh ‘Ali Jum’ah’s legal-meaning thought. The analysis relies on direct readings of the Qur’an, Sunan Ibn Mājah, Lisān al-‘Arab, Al-Mufradāt fī Gharīb al-Qur’ān, al-Ṭabarī, al-Qurṭubī, al-Sarakhsī, al-Kāsānī, al-Nawawī, and Ibn Qudāmah. Digital hidden fee practices are used as a contextual test case because they reveal how information, consent, compensation, and interface design shape the legitimacy of wealth transfer. The findings show that “consuming wealth” refers not merely to taking property, but to absorbing another party’s economic value through defective legitimacy. The article contributes operational indicators for reading digital transactions without reducing Qur’anic language to rapid legal labelling. Kajian Hukum Bisnis Islam kontemporer sering menghadapi transaksi digital dengan membawa kategori fikih yang sudah dikenal, seperti gharar, tadlīs, bāṭil, atau tarāḍī. Kategori tersebut tetap penting, tetapi perlu dijembatani melalui pembacaan yang hati-hati antara redaksi Al-Qur’an, tradisi tafsir-fikih, dan struktur transaksi modern. Melalui metode normatif doktrinal dan pendekatan semantik yuridis, tulisan ini merekonstruksi makna akl al-amwāl bi al-bāṭil melalui empat lapis analisis: makna leksikal, tradisi sosial, makna syar‘i dalam redaksi Al-Qur’an, dan indikator terminologis-operasional.  Analisis Empat lapis makna ini disintesiskan dari pemikiran Syaikh Ali Jum’ah yang bertumpu pada pembacaan langsung terhadap Al-Qur’an, Sunan Ibn Mājah, Lisān al-‘Arab, Al-Mufradāt fī Gharīb al-Qur’ān, al-Ṭabarī, al-Qurṭubī, al-Sarakhsī, al-Kāsānī, al-Nawawī, dan Ibn Qudāmah. Praktik hidden fee digital dipakai sebagai medan uji karena memperlihatkan bagaimana informasi, kerelaan, kompensasi, dan desain antarmuka membentuk legitimasi perpindahan harta. Temuan menunjukkan bahwa “memakan harta” tidak hanya berarti mengambil harta, tetapi menyerap nilai ekonomi pihak lain melalui legitimasi yang cacat. Sumbangan tulisan ini terletak pada penyusunan indikator operasional untuk membaca transaksi digital tanpa mereduksi bahasa Al-Qur’an menjadi label hukum yang tergesa.